2003
DOI: 10.1074/mcp.m300038-mcp200
|View full text |Cite
|
Sign up to set email alerts
|

Proteome Analysis of Human Vitreous Proteins

Abstract: Purpose: Various protein contents such as enzymes, growth factors, and structural components are responsible for biological activities in organs. We have created a map of vitreous proteins and developed a proteome analysis of human vitreous samples to understand the underlying molecular mechanism and to provide clues to new therapeutic approaches in eyes with proliferative diabetic retinopathy (PDR). Methods: Vitreous and serum samples were obtained from subjects with idiopathic macular hole (MH, 26 cases) and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
108
1
1

Year Published

2007
2007
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 100 publications
(114 citation statements)
references
References 31 publications
4
108
1
1
Order By: Relevance
“…Although its biological functions are incompletely understood, it seems to be a novel adipokine that may be involved in the local regulation of adipose tissue function [20][21][22][23]. ZAG has been recently identified by proteomic analysis in vitreous fluid from PDR patients [8,9]. In the present study we have confirmed this finding.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…Although its biological functions are incompletely understood, it seems to be a novel adipokine that may be involved in the local regulation of adipose tissue function [20][21][22][23]. ZAG has been recently identified by proteomic analysis in vitreous fluid from PDR patients [8,9]. In the present study we have confirmed this finding.…”
Section: Discussionsupporting
confidence: 85%
“…However, few proteome analyses in human vitreous fluid have been performed in the setting of diabetic eye disease [7][8][9][10][11], and no previous quantitative proteomic comparison has been reported. The aim of the present study was to compare the protein profile of human vitreous fluid from diabetic patients with PDR with that of vitreous fluid obtained from nondiabetic patients with idiopathic macular holes (MH), a condition in which, in contrast to PDR, the retina is not affected by neovascularisation.…”
Section: Introductionmentioning
confidence: 99%
“…A 2-D study of vitreous from patients with proliferative diabetic retinopathy and idiopathic macular hole showed characteristic protein patterns in these patients and led to the identification of numerous proteins as for example pigment epithelium-derived factor, prostaglandin-D2 synthase, and interphotoreceptor retinoid-binding protein [50]. These results confirm the findings of another study that analyzed the vitreous humor of diabetic retinopathy and macular hole patients by means of 2-DE.…”
Section: Proteomic Analysissupporting
confidence: 78%
“…Albumin and Ig make up 80% of the protein concentration in the vitreous. Most proteins that have been identified so far in vitreous humor, like albumin, transferrin, apolipoprotein, IgG, amino acid, and transthyretin [50,51], are also found in serum [52]. The vitreous contains a group of enzymes known as matrix metalloproteinases (MMPs) [53].…”
Section: Vitreous Humormentioning
confidence: 99%
See 1 more Smart Citation